(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The research gets its importance through the importance of the annual regulations in the taxation accounting and its efficiency to fulfill accounting justice under the effect of the financial changes and the truth of the activity of the taxable businesses .This through the problem of the research which is found in many objections about taxation accounting according to the annual regulations issued by the General Commission of Taxes , Their aim is to get the real benefits and to decrease the difference in opinions during the estimation to fulfill justice in distributing the burden of taxation . The research expose many conclusions and recommendations namely , the taxation justice fulfillment is not only in justice in distribution of taxation burden among taxpayers during the period of enactment but Also how to get taxes and show justice in application of taxation law . In spite of the comptroller’s agreement to the financial bills prepared by the taxpayer but the financial authority don’t regard these bills in accounting and this weaken the trust between the financial authority and the comptroller . The most important of the recommendations in the research is that justice in application and collecting taxes by the financial authority , the methods of collecting taxes are surely applied in a precise and active way .The comptroller must do his best professionally and morally to trust the General Commission of Taxes that depend on his reports to change his role from deputy for companies to a power to show truth to these companies .